(3eHGOF GdeMGSHI (B/s - (3YGQa, MSjf fGLjs ((3YeGf(B: s (3OGQ jGaG GdYdejI ddfTQ h GdJhRjY(B, s, 2006)
(3jYfi gPG GdcJGH (B-(3aj LRFg GdKGfj(B- (3HeHGOF GdeMGSHI, GSJceGdG deG LGA aj LRFg GdChd, hPdc ef NdGd SJI hMOGJ, LGAJ YfGhjfgG Ydi GdfMh GdJGdj(B: (3GdLQO, hLQO GdCUhd GdKGHJI, hLQO GdCUhd GdeJOGhdI, hLQO GdMSGHGJ GdhgejI, hCKQ GdJShjGJ GdLQOjI Ydi bGFeI GdONd hGdeQcR GdeGdj, hCNjQG GdWQb GdeMGSHjI hGdOaGJQ GdeSGYOI(B.s
(3edGMb U(B.199s
Keywords: (3GdOaGJQs; (3GdeMGSHIs; (3LQO GdMSGHGJs